FEMALE ENTREPRENEURS IN AGRIBUSINESS - Cvijanović, Janko M.; Vojnović, Boško; Lazić, Jelena (Economics of Agriculture, 2018)
Conducted survey analyzes the attitudes and thinking about the possibilities of launching women's agribusiness. The results indicate dissatisfaction with womens social status in the country and believe they are in a subordinate position in relation to male. There is interest in the rural areas to start their own agropreduzetničkog podzuhvata, those who are unemployed, and women who have a job, but to deal with jobs in agriculture. Potential entrepreneurs have experience in agriculture, but not sufficiently familiar with the functioning of agribusiness. For this reason, are willing to further educate and gladly accepted the grant grant support.